PERBEDAAN PERKEMBANGAN MOTORIK KASAR DENGAN STATUS GIZI KURANG DAN GIZI NORMAL PADA BALITA USIA 24 BULAN DI WILAYAH KERJA PUSKESMAS BADES - MARTANTYA ENY WIDYANTIKA; YESSY NUR ENDAH SARY; IIT ERMAWATI (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Malnutrition causes children to experience delays in growth and development. The purpose of this study was to determine differences in gross motor development between undernourished and normal nutritional status in toddlers aged 24 months in the working area of the Bades Health Center. Research design using cross-sectional. The population was toddlers aged 24 months in the working area of the Bades Health Center totaling 20 toddlers and using a total sampling of 10 toddlers with normal nutrition and 10 toddlers with malnutrition. The analytical method used an independent T-test. The results of the study of 10 toddlers with normal nutritional status showed that gross motor development was 100% normal. Whereas 10 toddlers with poor nutritional status got normal gross motor development 60%, 30% doubtful, and 10% abnormal. The conclusion of this study is that there are differences in gross motor development with undernourished and normal nutritional status in toddlers aged 24 months in the working area of the Bades Health Center with a p-value <0.001 less than 0.05. Further research is to examine the nutritional intake consumed by toddlers and toddlers' eating patterns.